Modernising speech audiometry: using a smartphone application to test word recognition. (3rd August 2018) - van Zyl, Marianne; Swanepoel, De Wet; Myburgh, Hermanus C.
Abstract: Objective: This study aimed to develop and assess a method to measure word recognition abilities using a smartphone application (App) connected to an audiometer. Design: Word lists were recorded in South African English and Afrikaans. Analyses were conducted to determine the effect of hardware used for presentation (computer, compact-disc player, or smartphone) on the frequency content of recordings. An Android App was developed to enable presentation of recorded materials via a smartphone connected to the auxiliary input of the audiometer. Experiments were performed to test feasibility and validity of the developed App and recordings. Study sample: Participants were 100 young adults (18–30 years) with pure tone thresholds ≤15 dB across the frequency spectrum (250–8000 Hz). Results: Hardware used for presentation had no significant effect on the frequency content of recordings. Listening experiments indicated good inter-list reliability for recordings in both languages, with no significant differences between scores on different lists at each of the tested intensities. Performance-intensity functions had slopes of 4.05%/dB for English and 4.75%/dB for Afrikaans lists at the 50% point. Conclusions: The developed smartphone App constitutes a feasible and valid method for measuring word recognition scores, and can support standardisation and accessibility of recorded speech audiometry.